Peranan Media Sosial Facebook Dalam Manajemen Publikasi Informasi Fakultas Tarbiyah Dan Ilmu Keguruan Iain Kendari - Nur Alim; Titin Retnawati; Syamsuddin Syamsuddin (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2018)
This study discusses the role of social media in the management of information publications Tarbiyah and Teacher Training Faculty of IAIN Kendari. The results of the study showed that the management of information publication at the Tarbiyah and Teacher Training Faculty of IAIN Kendari was divided into four stages. First, the planning stage, which includes analysis of information to be published, namely academic, student or general information, related parties involved in the publication, namely the leadership of the Tarbiyah Faculty and administrative staff. As well as media publications to be used, namely Facebook social media and print media. Second, the organizing stage, namely the administration of the Tarbiyah Faculty has five administrative staff in charge of organizing information publications. Third, the implementation stage, this information publication was carried out by administrative staff as well as the head of the Tarbiyah Faculty administration section through the use of print media and Facebook. The last stage is supervision, where faculty leaders are involved in supervising the publication of that information. The role of Facebook in the management of information publications at the Tarbiyah and Teacher Training Faculty of IAIN Kendari consists of three roles, namely information optimization, ease of publication and access to information, and has interesting features in information publication